Bridge Leadership: Gendered Consumerism and Black Women's Political Power within Early 20th Century "Don't Buy" Campaigns. Issue 3 (3rd July 2017) - Brown, Nicole Marie
ABSTRACT: This research surveys the literature around black consumerism and social movements, exploring the "Don't Buy Where You Can't Work" (DBWYCW) campaigns of the 1920s-1940s. The author examines the integral roles women played (as organizers, agitators, and beneficiaries) in various economic boycotts within the context of Belinda Robnett's theory of bridge leadership, with a particular focus on consumerism as a major vehicle through which African-American women engaged in movement work during the DBWYCW campaigns. This article challenges the erasure of women's leadership by reframing "Don't Buy" as a women's movement. Applying Robnett's bridge leadership theory to different eras, regions, and movements, we see how the Great Depression combined with activism in the gendered sphere of consumerism and facilitated the activism of black women. This paper also expands Robnett's conceptualization of professional and indigenous bridge leaders by identifying urban working class women within the "Don't Buy" movement who fit these leadership categories.